Overview of Green Energy as a Real Strategic Option for Sustainable Development - Armenia Androniceanu; Oana Matilda Sabie (Energies, 2022)
The global renewable energy landscape is changing rapidly. Green energies reduce greenhouse gas emissions, diversify the energy supply, and lower dependence on volatile and uncertain fossil fuel markets. The future looks promising for green energy sources, which are taking on an increasingly important role, especially in the current context, as governments are trying to identify viable solutions to the energy crisis and reduce dependence on fossil fuels. Worldwide, there is a growing interest in and support for green energy sources, a factor that could help accelerate the current energy transition. Despite these positive developments, much remains to be done globally to make the energy transition a reality. In this respect, the European Union member states have committed to a wide neutrality target by establishing an increase in the total share of energy from renewable sources to 55% (by 2030) and, at the same time, reducing the net greenhouse gas effect emissions by at least 55% until 2030 to reach the neutrality target by 2050. Green energy sources are essential for long-term efforts to mitigate climate change and will play an important role in improving energy security and accessibility. The efforts of every country to strengthen the energy sector through the development of green energies will reduce geopolitical risks and disproportionate external costs for society. The large-scale use of green energies will contribute to sustainable development. The objective of our research is to review the literature on green energy in the context of sustainable development by analyzing research conducted by various authors and international organizations on these topics. The period considered for this study is 2011–2020. Our research focused on the EU 27, but the review also took into account the results obtained by other countries worldwide, such as China, the USA, Norway, and Iceland. The main research method used was the analysis of scientific papers, studies developed by international organizations, and a wide set of agreements and political commitments assumed by different states for developing green energy as a solution for sustainable development. The obtained results show an interesting international debate about green energies and how they can contribute to sustainable development. This paper’s results also show that in 2019 at the global level, low-carbon energy sources, including nuclear power and renewable energy, accounted for 15.7% of primary energy (solar, wind, hydropower, bioenergy, geothermal and wave and tidal), while in 2021, for the EU 27, the share of energy from renewable sources reached 22%. According to international statistics, more than 90% of the governments of many countries are making investments to efficiently capitalize on green energy sources and to design new models of sustainable economic and social development, in order to lower pollution levels, reduce the dependence on fossil fuel imports and limit the climate change impact.